Model Upaya Hukum Dalam Kesalahan Objek Gugatan Sengketa Pertanahan - Solichah, Dewi; Sidarta, Dudik Djaja; Widodo, Erno; Aranggraei, Renda (RIO LAW JURNAL, 2025)
The government's failure to cause legal consequences, because of unilateral decisions. This is detrimental to its citizens, so it is called an unlawful struggle carried out by the rulers.This research aims to find out the unlawful acts committed by the rulers in this case, namely BPN government officials in issuing land certificates.Supreme Court Regulation Number 2 of 2019 explains related to unlawful acts committed by the government. In Chapter 1, Article 1 explains that government action means a dispute that arises in the field of government administration between citizens and government officials or other state administrators as a result of government actions.A lawsuit is a claim of rights filed by the plaintiff against the defendant through the court. If the Plaintiff's lawsuit to the court does not have a strong reason for the occurrence of a legal event, then the lawsuit in the trial is declared unacceptable or rejected (N.O). The NO decision is an unacceptable lawsuit. The plaintiff's lawsuit was due to an exception (rebuttal or rebuttal) from the defendant, which was then accepted by the panel of judges. This study aims to find out the lawsuit of Obscuur libel. In posita and petitum lawsuits do not support each other, it is also possible that the object of dispute is not clear. then the lawsuit in the trial was declared rejected by the panel of judges.The research method used is normative with a legislative approach (statue approach) and a case approach (case approach). Based on case number 68/G/2019/PTUN. SBY in this case, the Plaintiffs sued the Defendant, in this case a BPN government official at the State Administrative Court of Surabaya regarding a land dispute lawsuit on the government's decision that had issued 2 SHMs on behalf of the Defendant II Intervention.During the trial process, the panel of judges argued that the dispute that arose was that there was a discrepancy in the existing data, making the Plaintiffs' lawsuit against the object of the case ambiguous or arguably a lawsuit with the wrong object (Obscuur Libel).